Characterization and the effect of lignocellulosic biomass value addition on gasification efficiency. Issue 6 (November 2016) - Anukam, Anthony I; Mamphweli, Sampson N; Reddy, Prashant; Okoh, Omobola O
Value addition to lignocellulosic biomass materials such as sugarcane bagasse to produce multiple bio-based products which includes synthesis gas is becoming a dynamic research area. Pre-treatment techniques to improve the quality of biomass are essential for the successful application of the feedstock in energy production systems. This study investigated changes in the composition of sugarcane bagasse subjected to torrefaction as a preparation of bagasse for gasification. Characterization of the torrefied bagasse was undertaken in terms of proximate and ultimate analyses as well as in terms of energy value. The results were used to conduct a computer simulation of the gasification process of the torrefied bagasse. The gasification process results confirmed that torrefied bagasse is a suitable feedstock for gasification in terms of conversion efficiency, which was found to be approximately 42% when compared to untorrefied sugarcane bagasse, with a conversion efficiency of about 40% achieved in our previous study.